AN ANALYSIS OF INTERNATIONAL ECONOMIC LAW ON THE SETTLEMENT OF TRADE DISPUTES WITHIN THE WTO FRAMEWORK - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
International trade is a cornerstone of the modern global economy; however, differences in trade policy and protectionism often trigger disputes between countries that have the potential to disrupt the smooth flow of international trade. The World Trade Organisation (WTO), established in 1995, plays a central role in creating a rules-based multilateral trade governance system through the dispute settlement mechanism set out in the Dispute Settlement Understanding (DSU). This study aims to analyse the trade dispute settlement mechanism within the WTO framework and to identify implementation challenges and the need for reform from the perspective of international economic law. The research method employs a qualitative literature review using a juridical-normative approach. The findings indicate that the WTO’s dispute settlement mechanism provides legal certainty through a compulsory quasi-judicial system comprising a 60-day consultation phase, the formation of a panel within 6–9 months, an appeal to the Appellate Body within 90 days, and the implementation of the ruling. However, this system faces a serious existential crisis regarding the paralysis of the Appellate Body since December 2019 due to the United States’ refusal to appoint new members, which creates legal uncertainty and undermines the winning party’s right to enforce its rights. The imbalance of power between developed and developing countries, the difficulties in enforcing rulings against countries with dominant economic power, and the limited retaliatory capacity of developing countries reveal the structural weaknesses of the compliance mechanism. Reform of the WTO dispute settlement system is a priority, covering the review of appeals, the speed of proceedings, compliance rights, and capacity building. The Multilateral Provisional Appeal Arbitration (MPIA) arrangement promoted by the European Union provides an alternative dispute settlement mechanism to overcome deadlocks in the Appellate Body. This study emphasises the importance of institutional reform to ensure that the WTO remains a cornerstone of the global trading system.